Enhanced Enzymatic Hydrolysis of Cellulose From Substrate and Indole-3-Acetic Acid Content—During the Fruiting Body Differentiation Stage by Sodium Acetate Addition - Hou, Li-juan; Li, Zheng-peng; Li, Chang-tian; Lin, Jin-sheng; Ma, Lin; Jiang, Ning; Qu, Shao-xuan; Li, Hui-ping; Li, Yu (Frontiers in Fungal Biology, 2021)
Volvariella volvacea, with high commercial, nutritional and medicinal value, is widely cultivated in tropical and subtropical regions. The effects of supplementation on mushroom yield has been studied. We showed that the optimal application of sodium acetate (NaAc) was spray application of a 0.08% concentration during the substrate mixing stage which could increase yields by up to 89.16% and enhance the enzymatic hydrolysis of cellulose and hemicellulose from the substrate. For most enzymes tested maximum activity occurred during the fruiting body growth and development stage, which led to degradation of the substrate, increasing the available nutrients for mycelial propagation and fruiting body growth and development. Meanwhile, NaAc also significantly increased the indole-3-acetic acid (IAA) content in the early fruiting body development stage of V. volvacea, It was observed that IAA promotes not only plant primordium differentiation; but also the primordium differentiation of edible fungi. Furthermore, treatments with three acetate salts had an increase of yield by 30.22% on average. The mechanisms by which NaAc application may improve the yield of V. volvacea are discussed.